2006
DOI: 10.1289/ehp.8407
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Nitrates in Drinking Water: Maternal Exposure and Adverse Reproductive and Developmental Outcomes

Abstract: In this review we present an update on maternal exposure to nitrates in drinking water in relation to possible adverse reproductive and developmental effects, and also discuss nitrates in drinking water in the United States. The current standard for nitrates in drinking water is based on retrospective studies and approximates a level that protects infants from methemoglobinemia, but no safety factor is built into the standard. The current standard applies only to public water systems. Drinking water source was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
101
0
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 209 publications
(104 citation statements)
references
References 39 publications
(89 reference statements)
1
101
0
2
Order By: Relevance
“…There has already been a lot of literatures reporting drinking water nitrate pollution and its adverse effects on human health, but the causal relationship between exposure to nitrates in drinking water and adverse reproductive effects is still not clear (Manassaram et al 2006). However, the health risk assessment studies can provide useful information for water-quality management to ensure the general safety of drinking water for people.…”
Section: Health Risksmentioning
confidence: 99%
“…There has already been a lot of literatures reporting drinking water nitrate pollution and its adverse effects on human health, but the causal relationship between exposure to nitrates in drinking water and adverse reproductive effects is still not clear (Manassaram et al 2006). However, the health risk assessment studies can provide useful information for water-quality management to ensure the general safety of drinking water for people.…”
Section: Health Risksmentioning
confidence: 99%
“…There is some evidence from epidemiologic studies that exposure to nitrate from drinking water sources may increase the incidence of neural tube defects, oral cleft defects, limb deficiencies (Brender et al, 2004;Brender et al, 2013), cardiac defects (Cedergren et al, 2002), SGA and spontaneous abortions (Manassaram et al, 2006). Animal studies also show moderate associations with fetal loss, neonatal mortality, and decreased litters and live births (Manassaram et al, 2006).…”
mentioning
confidence: 99%
“…Nitrate levels, in particular, must be strictly regulated. Several epidemiological studies have shown a significant risk probability between elevated nitrate concentrations in drinking water and a battery of pathological states ranging from reproductive anomalies and human cancer, to endemic nephropathy and methemoglobinaemia (De Roos et al 2003;Fewtrell 2004;Manassaram et al 2006;Niagolova et al 2005). These findings, thus, highlight the need for more sustainable methods of production.…”
Section: Water Pollution Index (Wpi)mentioning
confidence: 99%